Pharmacoeconomic evaluation of the costs incurred by the ASP Messina for home therapy with liquid oxygen - Coppolino, Salvatore (Farmeconomia. Health economics and therapeutic pathways, 2010)
Chronic obstructive pulmonary disease (COPD) is a very frequent disease in all industrialized countries. The cost for the community includes cost for hospitalisations, doctor visits, home care, rehabilitation, loss of working days, etc. From a therapeutical point of view, an effective progression of therapy and patients survival can be obtained only by stopping smoking and by following a long term oxygen therapy. The aim of this retrospective study is to evaluate costs of liquid oxygen therapy performed at home. Obtained results are very encouraging because a part from being cheap they also provide a better evaluation of the prescribed therapy which can also be extended to gaseous oxygen.